Comparison of single and multiple functional communication training responses for the treatment of problem behavior. - Kahng, S W (2000)
Two functional communication training (FCT) conditions without extinction were compared to treat the problem behavior of a child with developmental disabilities. The individual was taught to emit a single FCT response to obtain one of six items delivered in a randomized order or multiple FCT responses that specified the exact item. Results showed that only the FCT-multiple condition reduced problem behavior and maintained alternative mands.